Two-dimensional magnetopolaron coupling to both homopolar and longitudinal optic phonons in the layer compound InSe - Howell, D; Nicholas, R; Langerak, C; Singleton, J; Janssen, T; Chevy, A (1989)
The authors have studied cyclotron resonance of the two-dimensional electron gas (2DEG) found in the layered semiconductor InSe at magnetic fields up to 30 T. The results show the first direct observation of resonant polaron coupling to a homopolar optic phonon, coupling via a deformation potential. They have also observed a large increase in the cyclotron effective mass as the LO phonon energy is approached, indicating the strongest polaron effects yet seen in any 2D system ( alpha approximately=0.3).